1987
DOI: 10.1128/aac.31.4.570
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between renal membrane binding and nephrotoxicity of aminoglycosides

Abstract: The kinetics of aminoglycoside binding to renal brush border and basolateral membrane vesicles from rat renal cortex were studied by using [3H]amikacin.[3H]amikacin binding to renal membranes was found to be a rapid, saturable process with a fourfold greater affinity for basolateral membranes than for brush border membranes (Kd basolateral = 607 ,uM; Kd brush border = 2,535 ,uM). Renal membranes prepared from immature rats (2 to 3 weeks old) exhibited a significantly lower affinity compared with membranes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 34 publications
5
63
2
Order By: Relevance
“…Thus, aminoglycoside derivatives with reduced tendency to accumulate in the renal cortex also proved less nephrotoxic (35). Given its central role in renal aminoglycoside uptake, megalin activity can be assumed to be a critical factor contributing to aminoglycoside-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, aminoglycoside derivatives with reduced tendency to accumulate in the renal cortex also proved less nephrotoxic (35). Given its central role in renal aminoglycoside uptake, megalin activity can be assumed to be a critical factor contributing to aminoglycoside-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in agree ment with the observation reported by Kacew (10), using gentamicin and PALP. It has been shown that spermine, a polyamine, reduced the gentamicin uptake in the rat kidney cortex (11) and that the binding of gentamicin to rat BBMs was inhibited by spermine (12). These observations suggested that reduction of intrarenal gentamicin level was associated with the inhibition of gentamicin binding to BBMs.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies indicated that the expression of angiogenin increased along with the progression of prostate cancer (15), and that the plasma angiogenin level was elevated in prostate cancer patients, particularly in hormonal refractory prostate cancer patients (13). Neomycin and neamine were found to inhibit the nuclear translocation of angiogenin (26), but neamine had much less toxicity than neomycin (27,28). PC-3 cells are a type of hormone-independent prostate cancer cell, and in the present study, it was demonstrated that neamine blocked the translocation of angiogenin in the PC-3 cells, with an effect that was comparable to DDP in PC-3 xenografts, but with much lower toxicity.…”
Section: Discussionmentioning
confidence: 99%